Factors influencing the uptake of antenatal care services among pregnant women in South Gaalkacyo district, Mudug region, Somalia - Haji, Omar A.; Suleiman, Mbaruk Abdulla; Juma, Joseph N. (International Journal Of Community Medicine And Public Health, 2022)
Background: Focused antenatal care addresses specific health conditions of pregnant mothers, therefore, improving health outcomes for mothers and infants including maternal and infant mortality. Somalia is among the first twenty African countries with the greatest maternal and infant mortality rates. Therefore, this study was conducted in the South Gaalkacyo district, Mudug region, Somalia, to investigate the factors influencing the uptake of antenatal care services among pregnant women. Methods: An analytical cross-sectional study with 385 participants. Data were collected using questionnaires, focus group discussions, and key informant interviews. Logistic forward linear regression analysis was used to examine the relationship between two or more variables of interest. And P-value below 0.05 was considered statistically significant. Bivariate and multivariate analyses were done. Qualitative data were analyzed using thematic analysis. Results: Of the study participants (52.67%) had poor knowledge of antenatal care and (88.1%) were satisfied with antenatal care services. There was a significant association between the study participants’ level of knowledge (p=0.0001), accessibility to health facilities (p=0.016), and health care workers’ attitudes (p=0.014) with the use of antenatal care attendance. From qualitative responses lack of support from husbands played an essential role in seeking antenatal health care. Conclusions: Underutilization of FANC was influenced by women’s knowledge, level of education, socio-economic and cultural factors as well as infrastructural factors. More education and awareness are required to educate women on the importance of utilizing ANC services.